Tell-tale bones - Haines, Carolyn (Haines, Carolyn. Sarah Booth Delaney mystery, 2023)
"Private Investigator Sarah Booth Delaney and her partner Tinkie are in Sheriff Coleman Peters's office, consulting Coleman about cold cases, when Elisa Redd storms in with a case of her own. She wants Coleman to reopen the investigation of her missing daughter, Lydia Redd Maxell, the heiress to a large fortune who disappeared along with her friend Bethany nearly seven years ago. Lydia and Bethany were rumored to be working as human rights organizers abroad, but Elisa suspects Lydia's problems might have stemmed closer to home. Now Lydia's husband, Tope, is set to inherit the fortune, and Elisa believes he's behind the disappearance. Sarah Booth and Tinkie soon connect the case to a series of mysterious disappearances over the years, as well as to a perplexing recurring dream. With another woman's life at stake, the friends follow an increasingly twisty trail all over Sunflower County, leading them to a tree and an empty grave in the county cemetery. A grave that's said to be haunted"--